2018
DOI: 10.1002/ajhb.23136
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence that androgen signaling is correlated with men's everyday language

Abstract: Together, these results suggest that T may influence social behavior by increasing the frequency of words related to aggression, sexuality, and status, and that it may alter the quality of interactions with an intimate partner by amplifying emotions via swearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 86 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…use and other sexually dimorphic phenotypes (Hoskin and Meldrum, 2018;Mascaro et al, 2018;Archer, 2019;Luoto et al, 2019a), providing a biological basis for the emergence of sexually differentiated traits. Many lines of research, including longitudinal research in humans, support this theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…use and other sexually dimorphic phenotypes (Hoskin and Meldrum, 2018;Mascaro et al, 2018;Archer, 2019;Luoto et al, 2019a), providing a biological basis for the emergence of sexually differentiated traits. Many lines of research, including longitudinal research in humans, support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the slightly higher frequency of anger-related words in male authors' novels (d = 0.32, Figure 1) does have some equivalents in psychological research. The use of anger-related words is positively correlated with circulating testosterone levels and with polymorphisms in the androgen receptor gene (Mascaro et al, 2018), which make cells more susceptible to the masculinising influence of testosterone. These findings indicate the existence of a plausible biological mechanism (Geniole et al, 2019;Luoto et al, 2019a) which creates sex differences in anger-related language use as well as other psychobehavioural sex differences, including peoplethings orientation, risk-taking, and theory of mind (Khorashad et al, 2018;Luoto, 2020b;Vaskinn et al, 2020;Luoto and Varella, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although lower F0 may be linked to higher testosterone circulating levels (Dabbs & Mallinger, 1999;Evans, Neave, Wakelin, & Hamilton, 2008), the immuno-handicap principle has yielded mixed results in humans (Roberts, Buchanan, & Evans, 2004;Boonekamp et al, 2008). Nonetheless, it has been reported that men plasma testosterone levels were positively correlated with sexual language and the use of swear words in the presence of their partners (Mascaro et al, 2018). Additionally, bioavailable testosterone was also found to be associated with the sound pressure level of the normal speaking voice in men and the softest speaking voice in women (Jost et al 2018).…”
Section: The Underlying Biological Quality Of Voicementioning
confidence: 99%
“…One source of inspiration for research aiming at biology-based models is that ‘[a]dvances in cognitive neuroscience and evolutionary science have increased our knowledge of mammalian sexual differentiation of the brain and how this process creates sex differences […] in various psychobehavioural traits in humans […], but the way in which such differences may be reflected in language use is not well known’ (Luoto, 2021: 1). A study by Mascaro et al (2018: 1) provided ‘preliminary evidence’ that higher testosterone levels in men ‘may influence social behavior by increasing frequency of words related to aggression, sexuality, and status, and that it may alter the quality of interactions with an intimate partner by amplifying emotions via swearing’. A related line of thought is that differences in language use between the genders correspond to underlying features of their psychology and cognitive styles: ‘Differences in the use of function words reflect differences in the ways that individuals think about and relate to the world.…”
Section: Introductionmentioning
confidence: 99%